An image analysis method for determining boiling front in minichannel heat exchanger - Rafałko Gabriela (EDP Sciences, 2021)
In this work a numerical method for determining boiling front in short time period of flow was presented. A non-stationary boiling in rectangular eleven minichannels (0.25 mm x 0.25 mm x 32 mm) was recorded using Phantom v1610 high speed camera with the speed of 6000 fps. In the algorithm correlation between subsequent frames was computed. Frames were divided into reference and test frames. In each iteration a part of a reference frame called ‘reference gate’ and moving part of a test frame called ‘moving gate’ were considered. A two-dimensional correlation coefficient was calculated. Such method allowed to identify the location of boiling front in each minichannel separately.